Wanted: Soft and friable witness. Mimotien ceramic artifacts - Noël Haidle, Miriam Noël; Heng, Sophady; Tausendfreund, Heike; Vonthein, Reinhard (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
Circular earthworks with outer walls and inner ditches surrounding a central platform are characteristic of Mimotien settlement sites, which are exclusively found in the red-soil area of East Cambodia and South Vietnam. Up to now, research on this late Neolithic to early Metal Age cultural complex concentrated on the location of the sites and their architectonical features. In this article a description of the Mimotien ceramic inventory is given, based mainly on samples excavated at Krek 52/62 compared to smaller samples and data from other earthworks. The analyses cover technological aspects such as the fabrics used, evidence for production techniques, surface treatment and decorative techniques. Typological analyses include rim, base, and complete vessel forms. The data do not allow a chronological ordering of the rim forms or the examined earthworks, but instead suggest either a short occupation of the sites or low rates of stylistic change together with local pottery traditions or preferences of form and decoration. Spatial analyses at Krek 52/62 show close areas for pottery production on the site and several depots of nearly complete vessels together with spindle whorls and other artifacts. An interpretation of these depots as offerings related to burials is likely, but cannot be definitely proven.The article will be available as a PDF in the near future.